Workload quantification in women`s soccer: does the starting status classification matter? - Miranda-Gonzalez, C.-E.; Rago, V.; Nakamura, F. Y.; Fernández-Romero, J. J.; Saavedra-García, M. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study explored methodological considerations in comparing accumulated workload across different starting status classification methods in professional women`s soccer. Specifically, we (1) described best-fit classification criteria and (2) compared accumulated workload data across methods used to categorize players based on the previous match exposure.